Dendritic phospholipid-based drug delivery systems. (26th January 2018) - Jiang, Lei; Chen, Weizhi; Zhou, Sensen; Li, Cheng; Zhang, Xiaoke; Wu, Wei; Jiang, Xiqun
Abstract : A class of new dendritic phospholipid compounds with different hydrophilic dendritic poly(l -lysine) peripheries from generations 1 (G1) to 3 (G3) (DPL-1 to DPL-3) were synthesised and nano-drug delivery systems based on these compounds were prepared (DPN-2 and DPN-3). Abstract : A class of new dendritic phospholipid compounds with different hydrophilic dendritic poly(l -lysine) peripheries from generations 1 (G1) to 3 (G3) (DPL-1 to DPL-3) were synthesised and nano-drug delivery systems based on these compounds were prepared (DPN-2 and DPN-3). DPL-1 couldn't self-assemble into nanocarriers. The size, TEM image, and the CD spectrum of DPN-2 and DPN-3 were experimentally examined. The effect of the peripheral structure of dendritic phospholipid-based nanocarriers on their biological performance and drug delivery efficiency was studied. In vitro cytotoxicity studies demonstrated that the DOX-loaded DPN-3 shows higher cytotoxicity against 4T1 cells and BGC823 cells than DPN-2. DOX-loaded DPN-3 also showed excellent behaviours in cell internalization and 4T1 multicellular spheroid penetration. The composition of the hydrophilic block in dendritic phospholipids affected the self-assembly behaviour, properties and delivery efficiency of the formed nanocarriers. This work will be helpful for building drug delivery systems with characteristics of high delivery efficiency and low cytotoxicity for clinical applications.